Pengembangan Pengujian Crashworthiness dengan Simulasi Numerik Menggunakan Model Impact Transferability - Felix Dionisius; Jos Istiyanto; Suliono Suliono; Yusup Nur Rohmat (Jurnal Teknologi Terapan, 2017)
Collision test is needed in transportation area in order to anticipate injuries of passangers when the accident occurred. Therefore, this test must be done for achieving standar requirements which is known by crashworthiness. This paper discussed about development of crasworthiness test by using modelling impact transferability by numerical simulation. The goal is to know the error of maximum deformation when given axial dynamic loading between numerical simulation and real experiment. Furthermore, analitic was used to validate duration of stress wave propagation from result of numerical simulation. This simulation used explicit finite element method by using PAM-Crash. The component of this research was impactor and impact of transferability with 80 and 27 kg of mass. The square tube-thin walled structure with holes as crush initator 3 mm of diameter was used as specimen. The result shows maximum deformation and duration of stress propagation error which are 3.90 % and 14.89 %.